Al-Sb-Ge phase change material: A candidate for multilevel data storage with high-data retention and fast speed. (December 2018) - Xue, Yuan; Song, Sannian; Yan, Shuai; Guo, Tianqi; Song, Zhitang; Feng, Songlin
Abstract: The phase change memory with Al-Sb-Ge alloy is investigated for the feasibility of embedded system and the potential possibility of multilevel data storage. The Al15 Sb53 Ge32 compound has a high crystallization temperature (333 °C) and outstanding data retention ability (260 °C). Ge atoms inhibit crystal growth to enhance thermal stability and Al15 Sb53 Ge32 contains sequential crystallization of Sb-rich and Ge regions in two-step crystallization process. Remarkably, the device presents a fast speed of 50 ns and endurance up to 2.3 × 10 4  cycles. At the same time, a reliable tripe-level resistance state of the phase change memory cell is observed. Graphical abstract: The phase change memory with Al-Sb-Ge alloy is investigated for the feasibility of embedded system and the potential possibility of multilevel data storage. Compared with conventional CGST, the selected composition of Al15 Sb53 Ge32 has a higher crystallization temperature and an outstanding 10-year data retention temperature, especially maintains the fast operation speed in devices. Besides, the thickness variation between amorphous and crystalline states is distinctly reduced below 3.6% prolonging the lifetime of a PCM device. TEM results prove that the grain growth is suppressed by Ge atoms, resulting in good thermal stability. Moreover, the sequential crystallization of Sb-rich and Ge regions may be advantageously used for multilevel data storage. For PCM cells based on Al15 Sb53 Ge32 material, a fast speed of 50 ns and a high endurance of more than 2.3 × 10 4 are all demonstrated to be realized and a reliable tripe-level resistance state of the phase change memory cell is observed. Unlabelled Image